Metode Earned Value Pada Pengendalian Proyek Pembangunan Gedung Sekolah SD Methodist-an Pancur Batu - Jenni Veronika Br Ginting Ginting (Forum Kerjasama Pendidikan Tinggi, 2020)
In a project it is necessary to identify a predictive data to obtain the provisions of the project being carried out in order to avoid the risk of failure or excess of the project that will be available, many mistakes and ignorance of the project control process that causes project work is not optimal , and often there is a lack of project funding and the time period provided is very long, thus making more losses, namely time and costs. So it is necessary to do analysis and calculation to find out how long the process takes and how much the cost will come out using the earned value (EV) method where this method will show the results of the CPI and SPI values ??which will later show the costs and how fast or slow the rate of a project and see the delay and the effect of the delay on the development of the construction project of the Pancur Batu Elementary School building.